Interacted Effect of Arbuscular Mycorrhizal Fungi and Polyamines on Root System Architecture of Citrus Seedlings - Qiang-sheng WU; Ying-ning ZOU; Chun-yan LIU; Ting LU (Journal of Integrative Agriculture, 2012)
Either arbuscular mycorrhizal fungi (AMF) or polyamines (PAs) may change root system architecture (RSA) of plants, whereas the interaction of AMF and PAs on RSA remains unclear. In the present study, we studied the interaction between AMF (Paraglomus occultum) and exogenous PAs, including putrescine (Put), spermidine (Spd) and spermine (Spm) on mycorrhizal development of different parts of root system, plant growth, RSA and carbohydrate concentrations of 6-m-old citrus (Citrus tangerine Hort. ex Tanaka) seedlings. After 14 wk of PAs application, PA-treated mycorrhizal seedlings exhibited better mycorrhizal colonization and numbers of vesicles, arbuscules, and entry points, and the best mycorrhizal status of taproot, first-, second-, and third-order lateral roots was respectively found in mycorrhizal seedlings supplied with Put, Spd and Spm, suggesting that PAs might act as a regulated factor of mycorrhizal development through transformation of root sucrose more into glucose for sustaining mycorrhizal development. AMF usually notably increases RSA traits (taproot length, total length, average diameter, projected area, surface area, volume, and number of first-, second-, and third-order lateral roots) of only PA-treated seedlings. Among the three PA species, greater positive effects on RSA change and plant biomass increment of the seedlings generally rank as Spd>Spm>Put, irrespective of whether or not AMF colonization. PAs significantly changed the RSA traits in mycorrhizal but not in non-mycorrhizal seedlings. It suggests that the application of PAs (especially Spd) to AMF plants would optimize RSA of citrus seedlings, thus increasing plant growth (shoot and root dry weight).